Technical Guideline: Rice Cultivation Reduces Costs, Improves Efficiency, Adapts to Climate Change in the Red River Delta - Department of Crop Production (2023)
The Department of Crop Production coordinated with the International Rice Research Institute in Vietnam to develop this technical guideline for rice-producing provinces in the Red River Delta. The guideline focused on reducing inputs, improving efficiency, reducing greenhouse gas emissions and adapting to climate change for rice production. The key components of the guidelines were (1) appropriate land preparation (including laser land levelling), (2) recommended varieties, adjusted crop calendar using CS-MAP, (3) crop establishment including recommendations for seed treatment, seedbed preparation, direct seeding and density, (4) crop care including recommendations for water management, fertilizer application and pest management, and (5) harvesting and postharvest management. In addition, the appendix of the guideline introduced several technologies and innovations such as Laser land leveling, on-tray seedbed (for machine transplanting), mechanized direct seeding, alternate wetting and drying irrigation, principles of fertilizer application, integrated pest management, harvest and postharvest technology and straw management.